2022
DOI: 10.3389/fimmu.2022.1026076
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of B7 family and its association with tumor microenvironment in uveal melanoma

Abstract: BackgroundUveal melanoma (UVM) is the most common primary intraocular malignancy in adults with a poor prognosis. B7 family is an important modulator of the immune response. However, its dysregulation and underlying molecular mechanism in UVM still remains unclear.MethodsData were derived from TCGA and GEO databases. The prognosis was analyzed by Kaplan-Meier curve. The ESTIMATE algorithm, CIBERSORT algorithm, and TIMER database were used to demonstrate the correlation between B7 family and tumor immune microe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 80 publications
1
1
0
Order By: Relevance
“…In recent years, numerous studies have demonstrated the crucial role of TIM in cancer progression and treatment outcomes [42][43][44]. Through GO/KEGG enrichment and correlation analysis, we found that m7G regulators are closely related to monocyte/macrophage system in the TIM, and subsequent single-cell analysis also con rmed this nding.…”
Section: Discussionsupporting
confidence: 71%
“…In recent years, numerous studies have demonstrated the crucial role of TIM in cancer progression and treatment outcomes [42][43][44]. Through GO/KEGG enrichment and correlation analysis, we found that m7G regulators are closely related to monocyte/macrophage system in the TIM, and subsequent single-cell analysis also con rmed this nding.…”
Section: Discussionsupporting
confidence: 71%
“…Furthermore, the interaction between UM tumor cells and CD8 + T-cells has been associated with poor prognostics and was stronger in BAP1 -mutant cells using the activation of ITGB2 (integrin subunit beta 2) and ICAM1 (intercellular adhesion molecule 1) [ 224 ]. Additional aspects, such as inflammatory pathways and alterations in B7 family expression, a group of cell surface proteins that plays a critical role in the regulation of immune responses, have been correlated with diverse characteristics in UM, including cytotoxic T-cell levels and methylation patterns [ 185 , 225 ]. Interestingly, STEAP1 (six transmembrane epithelial antigen of the prostate 1) exhibits high expression levels in various types of cancers, including bladder, colon, ovarian and prostate, playing a significant role in enhancing the invasive capabilities of tumor cells [ 226 ].…”
Section: Immune Microenvironmentmentioning
confidence: 99%